KONSEP KURIKULUM DAN KURIKULUM PENDIDIKAN ISLAM - Yudi Candra Hermawan; Wikanti Iffah Juliani; Hendro Widodo (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The curriculum is a program that is planned and implemented to achieve goals. Therefore the implementation of an education requires a concept that functions to be a tool that can always be changed according to the times. This study analyzes the concepts of the curriculum and curriculum of Islamic Education which includes understanding, curriculum components, and characteristics. The method used in this study is the library research method and the results obtained that the curriculum includes a variety of detailed student activity plans in the form of educational materials, suggestions for teaching and learning strategies, program settings to be applied, and things that includes activities aimed at achieving the desired target/goal. Similarly, in the Islamic Education curriculum must pay attention to a number of things including in accordance with human nature, including the interests of Muslims in general, are realistic, comprehensive, and continuity.